The Problem of Islamic Philosophy: Definitions and Origins - Ismail, Khalid; Wan Halim, Wan Mohd Amjad; Yahya Zikri, Soliha (Online Journal of Research in Islamic Studies, 2022)
Islamic philosophy is the product of a complex intellectual process in which Syrians, Arabs, Persians, Turks, Berbers and others took an active part. When we speak of Islamic philosophy we mean that a philosophy which development, and modalities, are essentially linked to the religions and spiritual fact of Islam. Sometimes the researchers of Islamic philosophy had also used the term Arabic Philosophy or Muslim Philosophy rather than Islamic. Islamic philosophy presents us with a number of unresolved questions having to do with its origin and its relation to Greek philosophy. However, the term Islamic philosophy preferable to the others. For example, in Islam, it has been explained in how Islamic philosophy was internally taken by the thought of the Quran through its propagation within the first Muslim community. It must also be included in the notion of the Quranic concept 'Sunatullah' or 'natural' which means the characteristic or trait given by God ‘alluding thereby to nature as something that is created by God It should not deny the importance of the science of metaphysics because it is very close to our reality. This study attempts to elaborate the development of Islamic philosophical ideas and analyses them from the Islamic theologico-philosphical views. This study examined the terms of the Islamic philosophy, analyze the function and structure of the terminology mentioned in the Qur'an since Allah's Commandments would have explicit and implicit wisdoms. This study is a qualitative study using content analysis method, as the subject determination. The results shown the terms which are issued in history of Islamic thought from various classical schools of Islamic thought which is Islamic philosophy will be defined it with regard to its fundamental characteristics mainly in connection to its origin.